Evaluation and optimization of nanosuspensions of Chrysanthemum coronarium and Azadirachta indica using Response Surface Methodology for pest management. (April 2022) - Hazafa, Abu; Jahan, Nazish; Zia, Muhammad Anjum; Rahman, Khalil-Ur; Sagheer, Muhammad; Naeem, Muhammad
Abstract: The rapidly emerging field of nanotechnology is considered an important achievement in the agriculture sector to increase the pest mortality rate and improve the crop production. The present study evaluates the novel pesticidal and anti-microbial activities of Chrysanthemum coronarium and Azadirachta indica in the nano-suspensions form. The anti-solvent precipitation method was used to formulate nano-suspensions proposed by Response Surface Methodology (RSM). Physicochemical nature of plant extracts and nano-suspensions was characterized through analysis of Zeta-sizer, FT-IR, and HPLC. Characterization results revealed a minimum particle size of 121.1 and 170.1 nm for Chrysanthemum coronarium and Azadirachta indica, respectively. The pesticidal activity of nano-suspension was performed against red flour beetle (RFB) and lesser grain borer (LGB) pests, which showed the maximum mortality rate of 100% with 100% concentration of plant extracts and nano-suspensions of Chrysanthemum coronarium and Azadirachta indica against both insects. In comparison, the combination of these both plant extracts revealed the maximum 100% mortality with a 50% concentration of nano-suspensions (mixing ratio 1:1) after 72 h. The antibacterial activity showed the maximum zone inhibition of 9.96 ± 0.17 and 14.17 ± 0.50 mm against S . aureus and E. coli with nano-suspension of Chrysanthemum coronarium, and 12.09 ± 0.11 and 14.10 ± 0.49 mm with nano-suspension of Azadirachta indica, respectively. It is concluded that individual nano-suspensions showed better pesticidal as well as antimicrobial activities than combinations. However, the constructed nanosuspension can be applied to control the plant pests and diseases simultaneously. Graphical abstract: Image 1 Highlights: The synergistic pesticidal effects of C. coronarium and A. indica were assessed. The CCD of RSM was used for the evaluation and optimization of nano-suspensions. Maximum mortality rate of insects was noted at 100% nanosuspensions concentration. Combination of both plants showed maximum pesticidal effect at 50% concentration. Individual nano-suspensions showed better pesticidal activity than combinations.